Impact of Untreated Dental Caries on Daily Performances of Children From Low Social Class in an Urban African Population: The Importance of Pain (2019)
To determine the impact of untreated dental caries on the oral health related quality of life (OHRQoL) of children from low social class in an urban Nigerian population. The study was conducted among 6 to 15-year-old pupils from low social class in randomly selected primary schools in Ibadan. An interviewer-administered Child Oral Impact on Daily Performances (C-OIDP) questionnaire was used to obtain required information. Oral examination was conducted by calibrated examiners. Data obtained were analyzed with SPSS and test of association done with Mann-Whitney U and Chi-square tests. A total of 1286 pupils participated in the study and 130 (10.1%) had untreated dental caries, out of which 26 (20.0%) had pain from carious tooth. The C-OIDP of children with dental caries was similar to that of children without caries [median 0.0 vs. median 0.0; r = -0.025; p=0.368]. The median COIDP (3.0) of those with untreated dental caries and pain was higher than that of participants with painless caries [0.0; r=-0.768; p<0.001]. There were significant impacts on all eight domains of the OHRQoL of those with untreated dental caries and pain (71.4 – 100.0%) when compared to those with painless caries (0.0 – 28.6%; p<0.05). Untreated dental caries significantly impacts on OHRQoL of pupils from low social class only when associated with pain